Prevention and management of post prostatectomy erectile dysfunction - Salonia, Andrea; Castagna, Giulia; Capogrosso, Paolo; Castiglione, Fabio; Briganti, Alberto; Montorsi, Francesco (Translational Andrology and Urology, 2014)
Sexual dysfunction is common in patients with prostate cancer (PC) following radical prostatectomy (RP). Review the available literature concerning prevention and management strategies for post-RP erectile function (EF) impairment in terms of preoperative patient characteristics, intra and postoperative factors that may influence EF recovery, and postoperative treatments for erectile dysfunction (ED). A literature search was performed using Google and PubMed database for English-language original and review articles, either published or e-published up to July 2013. The literature still demonstrates a great inconsistency in the definition of what is considered normal EF both before and after RP. Thus, using validated psychometric instruments with recognized cut-offs for normalcy and severity during the pre- and post-operative evaluation should be routinely considered. Therefore, a comprehensive discussion with the patient about the true prevalence of postoperative ED, the concept of spontaneous or pharmacologically-assisted erections, and the difference between “back to baseline” EF and “erections adequate enough to have successful intercourse” clearly emerge as key issues in the eventual understanding of post-RP ED prevention and promotion of satisfactory EF recovery. Patient factors (including age, baseline EF, comorbid conditions status), cancer selection (non- vs. uni- vs. bilateral nerve-sparing), type of surgery (i.e., intra vs. inter vs. extrafascial surgeries), surgical techniques (i.e., open, laparoscopic and robotically-assisted RP), and surgeon factors (i.e., surgical volume and surgical skill) represent the key significant contributors to EF recovery. A number of preclinical and clinical data show that rehabilitation and treatment in due time are undoubtedly better than leaving the erectile tissue to its unassisted postoperative fate. The role of postoperative ED treatment for those patients who received a non-nerve-sparing RP was also extensively discussed. Optimal outcomes are achieved mainly by the careful choice of the correct patient for the correct type of surgery. Despite a plethora of potential rehabilitative approaches, they should be only considered as “strategies”, since incontrovertible evidence of their effectiveness for improving natural EF recovery is limited. Conversely, numerous effective therapeutic options are available for treating post-RP ED.